INTEGRASI EXTREME PROGRAMMING DAN PROTOTYPE DALAM PENGEMBANGAN SISTEM POS ACCOUNTING DENGAN PENGUJIAN BERBASIS ARTIFICIAL INTELLIGENCE: INTEGRATION OF EXTREME PROGRAMMING AND PROTOTYPING IN THE DEVELOPMENT OF A POS ACCOUNTING SYSTEM WITH ARTIFICIAL INTELLIGENCE BASED TESTING - Nabela Putri Setiawan; Erba Lutfina; Galuh Wilujeng Saraswati; Resha Meiranadi Caturkusuma (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Advancements in information technology have had a significant impact on various sectors, including the business sector, which requires efficiency and accuracy in data management. Fresh Market Pantai Klatak is one of the companies that requires such improvements, as it still relies on a manual transaction management system, resulting in delays in reporting and errors in calculations. The development of a web-based Point of Sale (POS) Accounting System is expected to support transaction management and financial reporting at Fresh Market Pantai Klatak. The system development employs the Extreme Programming (XP) method combined with the Prototype approach during the planning and design phases to accelerate the development process and better meet user requirements. The integration of Extreme Programming (XP) and Prototype, supported by Artificial Intelligence (AI) during the testing phase, enables the development of a system that is responsive to user needs while improving code quality and user interface through AI-based automated validation. Unit Testing results indicate that the system functions properly with a success rate of 100%. Furthermore, User Acceptance Testing (UAT) results show an average score of 97%, which falls into the “very good” category, indicating that the POS Accounting System meets user requirements. Therefore, the developed POS Accounting System is feasible for use and is expected to improve operational efficiency and the accuracy of financial reporting at Fresh Market Pantai Klatak.